2013
DOI: 10.5114/pdia.2013.39437
|View full text |Cite
|
Sign up to set email alerts
|

The relation between type D personality and the clinical condition of patients suffering from psoriasis

Abstract: IntroductionType D personality is the last distinguished specific type of personality that is characterised by two dimensions: a tendency for feeling negative emotions – depression, anxiety, anger or hostility, and a tendency for withdrawal from the society. The latest research shows the significant role played by type D personality in the aetiology and course of a variety of diseases.AimThe article discusses the problem of the occurrence of type D personality in the group of patients suffering from psoriasis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 13 publications
7
12
0
Order By: Relevance
“…Patients with moderate to severe psoriasis were found to run about twice the risk of presenting Type D personality than healthy subjects. Patients with psoriasis have an increased frequency of Type D personality as compared to the general population, according to the results of Basinska et al . The prevalence of Type D personality in healthy volunteers in our study are consistent with the figures for population studies, roughly 23% .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Patients with moderate to severe psoriasis were found to run about twice the risk of presenting Type D personality than healthy subjects. Patients with psoriasis have an increased frequency of Type D personality as compared to the general population, according to the results of Basinska et al . The prevalence of Type D personality in healthy volunteers in our study are consistent with the figures for population studies, roughly 23% .…”
Section: Discussionsupporting
confidence: 92%
“…Patients with moderate to severe psoriasis were found to run about twice the risk of presenting Type D personality than healthy subjects. Patients with psoriasis have an increased frequency of Type D personality as compared to the general population, according to the results Table 6 Multivariate logistic regression analysis of potential factors linked to different dimensions of health-related quality of life of Basinska et al 23 The prevalence of Type D personality in healthy volunteers in our study are consistent with the figures for population studies, roughly 23%. 20,25,26 The increased frequency of Type D personality in subjects with moderate to severe psoriasis may have important implications: Personality, expressed as a relatively permanent feature, is a mediator between the stress produced by the environment and the debut, development and course of somatic diseases.…”
Section: Discussionsupporting
confidence: 87%
“…We found that psoriasis has a negative effect on patients’ psychological condition ( Figure 3 ). This finding corroborates other research findings suggesting that psychological functioning may be directly related to the patient's attitude toward the disease and the need to cope with disease on a daily basis, both of which lead to negative physical self-image and negative self-esteem [ 19 , 25 , 26 ]. Patients with psoriasis repress their emotional conflicts and have low self-acceptance [ 27 , 28 ].…”
Section: Discussionsupporting
confidence: 90%
“…Research has extensively supported the role of psychological risk factors both in the pathogenesis and outcomes of physical diseases among different patient populations (Lumley et al, 1997 , 2007 ; Taylor et al, 1997 ; Kudielka et al, 2004 ; Porcelli, 2009 ; Basinska and Wozniewicz, 2013 ; Solano, 2013 ). These studies have shown associations between individual's personality dimensions and a self-management of physical disease.…”
Section: Introductionmentioning
confidence: 99%